Solar urticaria: clinical characteristics, treatment effectiveness, long-term prognosis, and QOL status in 29 patients - Imamura, Shinya; Oda, Yoshiko; Fukumoto, Takeshi; Mizuno, Mayuko; Suzuki, Mariko; Washio, Ken; Nishigori, Chikako; Fukunaga, Atsushi (Frontiers in Medicine, 2024)
Introduction Solar urticaria (SU), a relatively rare skin inflammatory and photosensitivity disease, is often resistant to standard urticaria treatment. Quality of life (QOL) among SU patients has not been extensively explored. This study was performed to clarify the clinical features and effectiveness of therapies (e.g., hardening therapy) for SU and to determine QOL among SU patients. Methods The authors examined the characteristics, treatments, and QOL statuses of 29 Japanese SU patients using medical records and a questionnaire approach. Results Among 29 patients, H1 antihistamine therapy (H1) was effective in 22 (75.8%) patients. H2 antihistamine therapy (H2) was effective in three of seven (42.9%) patients. Ultraviolet radiation A (UVA) hardening therapy was effective in eight of nine (88.9%) patients. Visible light (VL) hardening therapy was ineffective in three of three patients. In one patient who underwent both UVA and VL hardening therapy, only UVA hardening therapy was effective. In the questionnaire, 18 patients (90%) reported some improvement compared with disease onset (four had complete remission, six had completed treatment although mild symptoms persisted, and eight were receiving treatment with moderate symptoms), whereas two patients reported exacerbation. Patients in complete remission had a mean disease duration of 4 years, whereas patients not in remission had a mean disease duration of 8.8 years. The mean Dermatology Life Quality Index (DLQI) score for the current status was 7.4. There was a correlation between DLQI and symptom/treatment status. However, neither DLQI and action spectra nor DLQI and treatments exhibited significant differences. Discussion The questionnaire revealed current QOL status and long-term prognosis in SU patients. Compared with disease onset, most patients showed improvement when assessed for this study. Both H1 and H2 should be attempted for all SU patients. UVA hardening therapy may be an option for SU patients with an action spectrum that includes UVA.